A Review of Transition Metal Compounds as Functional Separators for Lithium‐Sulfur Batteries. Issue 1 (2nd January 2023) - Zhang, Peng; Yue, Liangliang; Liang, Qiuyang; Gao, Heng; Yan, Qiong; Wang, Li
Abstract: Lithium‐sulfur (Li−S) batteries have great potential for the development of next‐generation high‐energy‐density secondary batteries owing to their high theoretical energy density, active material (sulfur) environmental friendliness, and low cost. However, their application is still impeded by the inherent sluggish kinetics and solubility of intermediate products of the sulfur cathode. Interface design is an important direction to address challenges in the development of Li−S batteries. The modification of the separator has been shown to effectively suppress the shuttling effect of physical hindrance or chemical bonding without affecting the utilization of active materials. This review encompasses the application of nanostructured transition metal oxides (TMOs), transition metal sulfides (TMSs), transition metal nitrides (TMNs), transition metal phosphides (TMPs), such as incorporating functional separators beyond the approach for preparing novel cathodes, and discusses their composites in a new multifunctional barrier layer for Li−S batteries. The objective properties of various metal compounds and the effect of the shuttle effect in particular on the electrochemical performance in Li−S batteries are highlighted, and give an outlook on the promising approaches for the construction of reliable Li−S batteries. Abstract : To improve the performance of LSBs, advanced coatings need to be developed for separator modification. This review summarizes the application of recently developed transition metal compounds for coating materials at various interfaces of LSBs. And existing challenges and the future development of interface design in high‐energy LSBs are summarized and prospected.